A aposentadoria se aproxima: e agora ?: percepções e expectativas de servidores do TJPE. - Silva, Joelma Lapenda Lopes da (2023)
This research had as general objective to understand, together with the servants of the Court of Justice of Pernambuco (TJPE), how the transition from the category of active worker to retired worker takes place. Specifically, we sought to: get to know the perceptions and feelings of TJPE servants about retirement, when they already have the time and age to do so and do not request it; understand how TJPE servants perceive the repercussions in the socio-family environment in view of retirement; and to analyze the expectations of TJPE servants about post-retirement and how they plan to adapt to it. The research method employed was qualitative research, using a socio-demographic questionnaire and a semi-structured interview as instruments. The participants were civil servants (of both sexes), working in the capital or in the interior of the State, who already had the time and age to retire, in the positions of technician, judicial analyst and bailiff. The results were evaluated using the Thematic Content Analysis Technique. The information found shows that, in fact, leaving the world of work is an impactful moment in people's lives, requiring a series of changes, new learning and readaptations. It was also observed that each person's perception of retirement is something very individual, as while some associated it with a moment of tranquility and being able to experience new and pleasurable things, others linked it to idleness, illness and death. The economic factor is a relevant aspect that appeared as a reason for delaying the request for retirement. More free time to dedicate to family members and to rest, travel and leisure was also pointed out as a positive factor with the arrival of retirement, although for some there is a fear of not knowing how to deal with all that time and there is a fear of not knowing deal with it and suffer. Preparing for retirement is an aspect that appeared to be important, however, it was noticed that the majority still haven't truly invested in this sense. With the data obtained, we sought to bring greater social and scientific visibility to the importance of preparing for retirement, as a way of contributing to avoid the negative effects that it may cause; collaborate with studies that help demystify the phenomenon of retirement; encourage actions that can contribute to early retirement planning, both within the scope of public and private institutions, as well as public policies.